(untitled) (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta’limning o’rni hamda rivojlanish omillari, 2025)
Аннотация: в статье описывается разнообразие кератофагов, насекомых кератофагов и наносимый ими вред быту и хозяйству, ценным вещам, распространения заболеваний. Abstract: This article discusses the diversity of keratophages, keratophagous insects, and the damage they cause to households, valuable items, and agriculture, as well as their role in the spread of diseases.